PENERAPAN SUMBER IDE BUDAYA KAWIN MASSAL MENGGUNAKAN KAIN TENUN CUAL BANGKA BELITUNG PADA BUSANA EVENING - Mr Zaryandi; Sri purwani; Prihatin Saraswati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
ABSTRACT The purpose of this research is to: (1) to find out, explore about The Culture of Mass Mating as a source of ideas on the manufacture of evening clothing that will be applied in the design of illustrations, (2) to preserve a regional culture in the manufacture of evening clothing using traditional Bangka Belitung fabrics namely Woven Cual fabrics, (3) know the results of applying the source of the idea of Mass Mating Culture In evening clothing on the sleeves bishop, peplum details, hairpiece/headdress in the form of umbrellas. This research is qualitative research with a descriptive method using the results of research as is. The method of determining the subject using sampling studies with non-random sampling techniques because in sampling the author has determined the research subject first. Data collection method using the results of experiments. The sensory test method in this study using organoleptic testing or assessment based on the sensing process that is the sense of vision. Documentation method in the research using primary documentation in the form of experiment results and the form of photos of experiment results and secondary documentation in the form of books, journals, magazines and related articles. From sensory test data with a focused review from the angle of Beauty Design and Finishing Technique, evening fashion that uses the source of the idea of mass mating culture made from woven fabric cual is very good. This is evidenced by the results of all panellists 100% stated the results of a beautiful design and the finish is very neatly visible from the outside and the inside